Tinjauan Hukum Terhadap Penerapan Restorative Justice pada Tindak Pidana Penganiayaan dan Pengeroyokan di Wilayah Polres Jakarta Selatan - Irawan, Donny; Zain, Subhan; Sudarto, Sudarto (Neolectura, 2024)
A criminal act is an act of a person of his own will or of another person carried out by him and the behavior is an act that is prohibited and at the same time gives rise to a criminal responsibility by the perpetrator of the act and the act itself. Every act of criminal abuse and assault results in physical, psychological, sexual and/or neglectful misery or suffering, including threats to commit acts. coercion or deprivation of liberty in an unlawful manner is a criminal act of abuse and assault. A person who commits a crime of allowing, committing, ordering to do, participating in committing violence against criminal acts of abuse and assault must still be responsible because a person cannot be held responsible and sentenced to a criminal offense if he does not commit a criminal act. To be further examined how the regulation of criminal acts of abuse and assault allows, orders to do or participates in committing violence, then based on Indonesian criminal law and how the criminal responsibility of children who commit the crime of allowing, ordering to do or participating in committing violence against criminal acts of abuse and assault. The research method used in this study is the normative legal research method, from the results of the study it was found that the regulation of criminal acts of children who allow, order or participate in committing violence, criminal acts of abuse and mob violence in Article 76C in conjunction with Article 80 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and criminal responsibility of children who commit criminal acts of allowing, ordering or participating in committing violence against children to death by serving a maximum of half of the maximum prison sentence for adults as regulated in Paul 81 paragraph (2) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Clarifying the meaning of acts of violence in the KUI IP. Legislation, Government Regulations, Permenkumham and the Government must form legislation, government regulations, Permenkumham that are even stricter in providing sanctions for perpetrators of criminal acts of abuse and mob violence